Assessment of Depression Levels Using COVID – 19 Depression Scale Among Health Care Workers Due to COVID – 19 Pandemic: Original article - B Deepika; K Harini; Sri Niranchana; Anusha, Divvi; Kengadaran, Shivashankar (International Journal of Social Rehabilitation, 2024)
Introduction: The emergence of the Novel Severe Acute Respiratory Syndrome Corona virus-2(SARS-Co) better known as COVID -19 was first detected in the end of December, 2019 and its outbreak remains as the greatest medical challenge and a global threat to the humankind in recent times. Amidst the chaos, caused among the people by the pandemic the health care workers are the group of people aiding in the screening and treatment of this infectious condition throughout the continents. Hence, the present study deals with the assessment of depression levels using COVID19 Depression Scale(CDS) among Health care workers due to COVID19 pandemic. Methodology: A cross sectional study was conducted among 100 healthcare workers in Pondicherry. A simple random technique was adopted 100 participants. The assessment of depression levels was done using COVID-19 depression scale (CDS) which is a structured scale designed to measure the depression levels by using 4 different criteria. Data was entered in Microsoft excel spread sheet and analyzed using SPSS software (version 20). Descriptive statistics were used. Results: On an average, among the Health Care Workers, about 17.2%(n=17) had mild depression, 25.3%(n=25) had moderate depression, 46.5%(n=46) had intermediate depression, 11.1%(n=11) had high depression. 15% of doctors had high depression 6.7% of the dentists had high depression and 8.3% of nurses had high depression. Conclusion: This study shows that there is a definitive level of depression among the health care workers of Puducherry. Multidisciplinary mental health teams must be set up both at national and regional levels especially in areas harbouring more COVID-19 cases, to provide quality psychological support to the health care workers.